2015
DOI: 10.11604/pamj.2015.20.60.5864
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular outflow tract tachycardia worsened during pregnancy

Abstract: We report the case of a 35 years old woman without underlying heart disease who was diagnosed with a right ventricular outflow tract tachycardia worsened during pregnancy. The diagnosis of ventricular tachycardia was made early in her pregnancy course but the patient had symptoms three months earlier. Her disease course was marked by rhythmic storms during the second trimester of pregnancy that led to three hospitalizations accounting for about two weeks in total. The combination of nadolol 80 mg and flecainid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…RVOT tachycardia is the most common form of idiopathic ventricular tachycardia, which may occur in the absence of structural heart disease 24,30 . It is suggested that high level endurance exercise training 14,27 and pregnancy 31 may provoke idiopathic RVOT tachycardia. Yet, RVOT tachycardia can also occur in patients with ARVC/D 14,32 .…”
Section: Discussionmentioning
confidence: 99%
“…RVOT tachycardia is the most common form of idiopathic ventricular tachycardia, which may occur in the absence of structural heart disease 24,30 . It is suggested that high level endurance exercise training 14,27 and pregnancy 31 may provoke idiopathic RVOT tachycardia. Yet, RVOT tachycardia can also occur in patients with ARVC/D 14,32 .…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the heart rate could be due to stress, sympathetic stimulation, or hormonal phenomena during pregnancy [ 22 ]. Kambire et al reported a case of right ventricular outflow tract tachycardia that worsened during pregnancy, suggesting that ventricular tachycardia may be exacerbated by pregnancy, with the cause ranging from congenital heart disease to peripartum cardiomyopathy [ 23 ].…”
Section: Discussionmentioning
confidence: 99%